The Case for Depositor Preference. (Washington, D.C. : International Monetary Fund, 2020)
This technical note and manual (TNM) addresses the following issues: advantages and disadvantages of different types of depositor preference, international best practice and experience in adopting depositor preference, and introducing depositor preference in jurisdictions with or without deposit insurance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet